Meningkatkan Aktivitas Dan Hasil Belajar Menggunakan Model Problem Solving Dan Numbered Head Together Di Kelas 5 SDN 3 Sungai Danau - Yuni Rahmalian; Mahmuddin (CV. ITTC INDONESIA, 2023)
The issue in this study is low understudy action, low understudy learning results. Hence, one of the endeavors to expand movement and learning results is through the Critical thinking Model (PS) and Numbered Head Together (NHT). The reason for this study was to depict educator exercises and dissect understudy exercises and understudy learning results. This review utilized a subjective and quantitative methodology with the kind of Study hall Activity Exploration (PTK) which was completed in four gatherings. The examination subjects were 5th grade understudies at Sungai Danau Tanah Bumbu Primary School for the 2022/2023 scholastic year, with a sum of 29 understudies. Information created from perceptions and meetings, then broke down utilizing elucidating procedures and portrayed as tables and diagrams. The outcomes showed that the educator's movement at each gathering generally expanded, getting the models